?EFFECTS OF PROCESSING ADDITIVES ON THE PROPERTIES OF NATURAL RUBBER (NSR 20) - Popoola, A V; Ogedengbe, E (Biological Sciences - PJSIR, 1998)
Commercial sample of unprocessed natural rubber (polyisoprene) NSR 20 compounded into base polymer was pro- into sheets using various vulcanizing and plasticizing additives. Physical testing of the vulcanized rubber samples was carried out on an Instron testing machine for tensile properties.Tests were also carried out to assess the effects of plasticizer additives on the rheological properties of the processed rubber.Tensile strength and modulus at break % increase steadily with increase in sulphur level up to 5 pphr (parts per hundred rubber) and fall gradually when sulphur level exceeds 10 pphr but elongation at break decreases accordingly. Dioctysebacate (DOS) and Dioctyladipate (DOA) are quite effective as plasticizers in reducing the viscosity, Tg (glass transition temperature) and hardness of the rubber while Dibutoxylethoxylethyladipate (Bisoflex III) is less effective.